TINDAK TUTUR DAN PELANGGARAN MAKSIM PERCAKAPAN PADA NOVEL HARRY POTTER AND THE SORCERER’S STONE - Ida Ayu Panuntun (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2012)
One  of  the  most  important  aspects  of  the  language  use  is  in  the  people’s implicature  that  can  be  shown  in  the  conversation.  As  in  fact,  many students  do not understand the conversational maxims that cause the implicature. Based on its background,  this  study  uses  a  novel  entitled  “Harry  Potter  and  the  Sorcerer’s Stone” to enrich the understanding of conversational maxims. This study has two purposes. The first is to identify the maxims which flout the cooperative principle in term of meanings. The second is to identity the speech act of each implicature. The  method  used  in  this  study  was  descriptive  qualitative  with  cooperative principle analysis approach. The objects of the study were the conversations. The findings show  that  there  are  47.4%  conversations  which  flout  quaqntity  maxim; 13.2% conversations which flout quality maxim; 31.6% conversations which flout relevance maxim and 7.9% conversations which flout manner maxim. Meanwhile the  next  finding  related  to  the  speech  act.  There  are  expressive,  directive  and representative. It  is  suggested  that  these  findings  can  be  used  as  a recommendation for researchers to use other novels as the object of the study and other  point  of  view,  such  as  to  describe and  explain  the  level  of  difficulty  in  the conversational maxims. Keywords: speech act, cooperative principle, novel